2012
DOI: 10.3390/molecules17089668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flavonoid Contents and Antioxidant Capacity of the Aerial Parts of Common and Tartary Buckwheat Plants

Abstract: The analysis of major and minor flavonoids, and antioxidant capacity of stems, leaves, flowers, unripe seeds and ripe seeds of common and tartary buckwheat plants collected during different growth periods was addressed in this study. The highest rutin contents were observed in flowers and leaves collected from common and tartary buckwheat at early flowering as well as flowering and seed formation states. A low quercetin contents were found in all studied aerial part of buckwheat plants. Quercitrin (quercetin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 28 publications
4
76
1
5
Order By: Relevance
“…Bamby). These results are higher than the results of Zielińska et al (2012a), who determined rutin in seeds of common and tartary buckwheat in the amount of 43 and 13 500 mg/kg DM, respectively. The analysis results show that there are highly significant differences in total polyphenol and rutin contents as well as in total antioxidant capacity between the studied buckwheat cultivars.…”
Section: Resultscontrasting
confidence: 73%
“…Bamby). These results are higher than the results of Zielińska et al (2012a), who determined rutin in seeds of common and tartary buckwheat in the amount of 43 and 13 500 mg/kg DM, respectively. The analysis results show that there are highly significant differences in total polyphenol and rutin contents as well as in total antioxidant capacity between the studied buckwheat cultivars.…”
Section: Resultscontrasting
confidence: 73%
“…Li et al [30] showed that leaves of buckwheat contained rutin, but they did not identified quercetin. Also Zielińska et al [31] reported that leaves of common and tartary buckwheat were a good source of rutin. The results of Kreft et al [32] revealed that buckwheat beer and vinegar contained a negligible amount of this polyphenolic compound.…”
Section: Discussionmentioning
confidence: 99%
“…Zielińska et al [2010] demonstrated a low contribution of rutin in the antioxidant potential of buckwheat seed products (fl our, hull, groats and sprouts) and concluded that the focus on rutin as the main antioxidant in buckwheat can be overestimated. For whole common buckwheat seeds, the contribution of rutin in the antioxidant capacity was estimated at 25% [Zielińska et al, 2012]. Because lipophilic antioxidants, e.g.…”
Section: Introductionmentioning
confidence: 99%